The role of Psychology in the treatment of adolescent drug addiction (Research, Society and Development, 2020)
This study is a research whose main objective was to understand drug addiction, more specifically the drug addiction in adolescence, from a Psychology perspective. The aim of this paper was to investigate in the literature what is the role of psychology in drug addction treatment during the adolescence. Besides that, it is also possible to learn the methods used by psychologists to treat drug addiction in adolescents and to identify possible risk factors that encourage the use of narcotics in adolescentes and identify possible risk factors that encourage the use of narcotics in adolescence. Among the results obtained, it is relevant to highlight the role of the Psychology professional in the treatment of drug addiction in adolescence, the impact that the problem has on the family and social environment, and the relevance of the action of public policy actions to combat drug abuse. The study allowed na observation of the main aspects that influence the increasing use of narcotics during adolescence and the impacts caused from this fact based on the perspective of Psychology.